Pengaruh Hambatan Samping Terhadap Kapasitas Jalan (Studi Kasus Jalan Imam Bonjol dan Jalan R.A Kartini Bandar Lampung - Destriana, Revina; Karami, Muhammad; Herianto, Dwi (Universitas Lampung, 2020)
The existence of roads is a tool to serve the movement of activities in urban areas. The problems that occur on the Jl. Imam Bonjol and Jl. RA Kartini is the number of vehicles that carry out activities in and out on the left and right of the road, the slow flow of vehicles, pedestrians, and the number of people who make buying and selling transactions on the right and left sides of the road which causes congestion and queues of vehicles that result in the road section is not functioning properly, namely as the main road in the city of Bandar Lampung. For this reason, it is necessary to analyze the effect of side barriers on the capacity of these roads.The purpose of this study is to identify the effect of side barriers on road capacity, the volume of vehicles on Imam Bonjol and RA Kartini roads and the difference in travel time required on the Imam Bonjol and RA Kartini roads in the morning and evening. To achieve a goal, the target is What is done is expected to be able to help the proper handling of road performance improvement and to determine the magnitude of the influence of side friction factors on the capacity of roads that occur in urban areas, especially Imam Bonjol and RA Kartini roads. And the method used in this study usesGuidelines for Indonesia's Road Capacity (PKJI) 2014.The output obtained from the research is the very high effect of side friction (ST) on the Imam Bonjol and RA Kartini roads resulting in a decrease in capacity, namely the Imam Bonjol road has decreased capacity by 27.73% and the RA Kartini section has decreased capacity. amounted to 26.27%. From the results of the survey conducted, it was found that the volume of heavy traffic affected the value of the capacity on the roads of Imam Bonjol and RA Kartini along 200 meters respectively.It was found that the effect of very high side friction (ST) resulted in an increase in travel time, namely on roads. Imam Bonjol the travel time needed is 3 minutes 10 seconds (3.78 km / hour) and on the RA Kartini road section it is 57 seconds (12.63 km / hour).Keywords : Side Obstacles, Traffic jam, time and capacity.